Specificity of Relations between Regulatory-Dynamic Variables of Soiability in Latin American and Russian Students - O O Katchurina (Peoples' Friendship University of Russia (RUDN University), 2012)
The specificity of the relations between the regulatory-dynamic variables of sociability in the Latin American and Russian students is analyzed in the article. The ethno-psychological peculiarities in the ratios of the dynamic, emotional and regulatory properties of sociability in the two compared groups of students are revealed.